Adjustment of entry fees to the Galapagos National Park: Tourist attitudes and perceptions - Carlos Silva-Zambrano; Claudia Aravena; Eoin McLaughlin; Cesar Viteri (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2025)
This policy brief summarises key findings from the project Hidden Barriers to Conservation-Addressing Social Acceptability to Enhance Effective Management in the Galapagos Marine Reserve, conducted by Heriot-Watt University with the support of The Rufford Foundation, in collaboration with the Charles Darwin Foundation and the Galapagos National Park Directorate. It discusses tourist attitudes towards changes in entry fee policies in the Galapagos National Park. As one of the most biodiverse places on Earth, the Galapagos face several challenges for its conservation and sustainable development, including increased anthropogenic pressure due to the rapid growth of tourism. To address this, entry fees have been adjusted for the first time in 25 years, with the aim of regulating visitor flow while generating additional resources for the national park management. Entry fees are a key tool for managing nature-based tourism, and their adjustment is essential to restoring their effectiveness. However, little is known about how these changes impact the tourism sector. By analysing tourist attitudes and perceptions during the fee increase period, this study provides recommendations to guide future entry fee adjustments and the allocation of additional funds collected. Ultimately, these recommendations aim to facilitate an effective and timely implementation of entry fee policies, supporting both the conservation of biodiversity and the sustainable management of the Galapagos.
Keywords: H23; Q26; Q57; 330; public attitudes; individual preferences; tourism management; protected areas